ANALISIS PENGENDALIAN PEMANFAATAN RUANG DI KOTA SALATIGA - Istianah Setyaningsih (Jurnal Reformasi Administrasi : Jurnal Ilmiah untuk Mewujudkan Masyarakat Madani, 2016)
Salatiga is one of the cities that were in the area of nationally strategic Kedungsepur, and has potential of natural resources and infrastructure and facilities provide opportunities for Salatiga city to grow and evolve and one of them with carrying out development. High levels of development making Salatiga city get in trouble in terms of the use of space, among athor limited land which resulted in the opening of agricultural lamd the offense of between spatial plan from the utilization of space, and weal law enforcement againts violations.The focus and purpose of the research is to describe and analyze how the implementastion  controling the utilization space in Salatiga City.In addition to describe and analyze the factors that contribute to the implementation of controling the utilization space in Salatiga space. The theory used in this research is Public Administration, Public Implementation, and control of spatial use of space. This research uses qualitative research type by using doamin analysis method, analysis of the taxonomy and analysis of overlay map within view the implementation of controling the utilization space in Salatiga space. The respondent who used, among others Dinas Cipta Karya dan Ruang Kota Salatiga, Satuan Polisi Pamong Praja Kota Salatiga and the people of Salatiga city.The result of this research explains that the implementation of the control usage space in the Salatiga city is implemented in stages of monitoring and curbing. But in the process of implementation encountered obstacles related to managing human resources, implementing agencies coordination, process evaluation of utilization of space, the implementing agencies carried out socialization, budget execution control and the lackof participation from people of teh Salatiga city. This caused the control usage space in the Salatiga city not running optimally.Implementation of the control usage space in the Salatiga city can be maximized by means of the control activities in society involve the utilization of space, increasing the budget for tha activity control, improve coordination of agencies implementing, improving socialization about controling the utilization of space and increase the involvement of private and the people of the Salatiga city,